2022
DOI: 10.31234/osf.io/3tcvs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unique Cognitive and Emotional Profiles of Interpersonal Gratitude and Spiritual Gratitude

Abstract: Gratitude is a prototypical emotional response when life’s blessings come from the intentional goodwill of other people, but many also attribute good experiences to the intervention of God, gods, a Higher Power, or other benevolent spiritual forces. This study investigated the differences between how United States participants (N = 610) experience interpersonal gratitude and spiritual gratitude. Compared to interpersonal gratitude, spiritual gratitude experiences were less often attributed to human action, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…People may be grateful to God for nature. This way of experiencing gratitude has been observed in other domains of people's lives, in which people are grateful for God's blessings in their life (e.g., Aghababaei & Tabik, 2013;Emmons & Kneezel, 2005;Krause, 2006;Krause & Hayward, 2015Nelson et al, 2022;Rosmarin et al, 2011;C. White et al, 2023;Wilt & Exline, 2022).…”
Section: Potential Moderation By Religious Contextmentioning
confidence: 63%
“…People may be grateful to God for nature. This way of experiencing gratitude has been observed in other domains of people's lives, in which people are grateful for God's blessings in their life (e.g., Aghababaei & Tabik, 2013;Emmons & Kneezel, 2005;Krause, 2006;Krause & Hayward, 2015Nelson et al, 2022;Rosmarin et al, 2011;C. White et al, 2023;Wilt & Exline, 2022).…”
Section: Potential Moderation By Religious Contextmentioning
confidence: 63%
“…Tsang, 2006); in contrast, (2), (5), and (6) were "privilege/no gratitude" conditions (cf. White et al, 2022). Finally, (1) was the neutral baseline, lacking either a benefit or a privilege salience reflection task.…”
mentioning
confidence: 99%
“…Underscoring gratitude's interpersonal nature, Yu et al (2017) documented a distinct response pattern in the brain's reward centers when participants believed that others voluntarily chose to offload participants' exposure to painful stimuli onto themselves versus when a computer "chose" comparable pain reduction. Moreover, White et al (2022) showed that gratitude maps onto attributing causality for positive outcomes to an external, personal source (vs. circumstances or oneself). Preemptively inducing gratitude may therefore mitigate the aversive consequences of salient gender-based privilege among men.…”
mentioning
confidence: 99%